Analisis Manfaat dan Tantangan Implementasi Teknologi dalam Pembelajaran: Sebuah Tinjauan Pustaka (Asosiasi Riset Ilmu Pendidikan Indonesia, 2026)
The use of technology in learning represents a crucial innovation in education, evolving alongside advancements in science and technology. The utilization of technology allows the learning process to become more interactive, flexible, and capable of adapting to the needs and characteristics of students. However, in practice, the implementation of instructional technology still faces various challenges, such as limited access to technology, low educator competence, and uneven readiness among educational institutions This study aims to examine the utilization of technology in learning, identify the benefits obtained, and analyze the challenges faced during implementation. The research method employed is a literature study with a qualitative approach, conducted through a review of various literary sources including books, scientific articles, and relevant research findings discussing the application of educational technology The results of the study indicate that the use of digital technology such as interactive multimedia, e-learning, and augmented reality is able to enhance learning effectiveness, student motivation, and the quality of learning outcomes. Nevertheless, obstacles remain in the form of technological facility gaps, a lack of teacher training, and the slow adaptation of educational institutions to technological developments. The conclusion of this research emphasizes that the application of technology in learning requires adequate infrastructure support, the improvement of educator competence through continuous training, and supportive educational policies to ensure that technology utilization can function optimally and sustainably.